MELATIH KEARIFAN INTELEKTUAL, EMOSIONAL, DAN SPIRITUAL PEMUDA GUNA MENGHADAPI PASAR BEBAS ASIA TENGGARA (MASYARAKAT EKONOMI ASEAN-MEA) - Andriani, Ana Andriani (Universitas Pendidikan Indonesia, 2016)
Youth is the hope of the nation that has a great responsibility for the future of the nation and country. A heavy burden on his shoulders has its own consequences, which the youth must be able to work and participate in development. Youth with all its potential has an important role in the future life. Therefore, the youth must master in soft skills and hard skills to be able to compete with other nations in the world. This paper describes the role of the youth to build a nation with wisdom, intellectual, emotional, and spiritual needs to have to face the various challenges of the times. Similarly, the readiness of the youth needed both physically and psychologically in order to welcome the free market of Southeast Asia / ASEAN Economic Community (MEA) is imminent. Youth with all the benefits expected to be the generation that is better than the previous generation, so that the nation still exist in the eyes of the world. Through the study of literature describes how the role of youth in the face of global challenges to be enactment of Asian Economic Community (MEA) will be presented very competitive. In addition to the example and support that should be provided by parents, governments, and private parties as well as other related exercise wisdom, intellectual, emotional, and spiritual youth should be conducted on an ongoing basis in order to anticipate things that are not desirable. Global challenges and competition from various nations is expected to increase wisdom, intellectual, emotional, and spiritual.Keywords: Wisdom intellectual, emotional, spiritual, youth, Southeast Asian Free Market (Economic Community Asia-MEA)